School Breakfast Club Programs in Australian Primary Schools, Not Just Addressing Food Insecurity: A Qualitative Study. (August 2020) - Jose, Kim; MacDonald, Fiona; Vandenberg, Miriam; Williams, Julie; Abbott-Chapman, Joan; Venn, Alison; Smith, Kylie J.
Background. Many Australian primary schools have established school breakfast clubs (SBCs) to address concerns about children arriving at school hungry and the subsequent impact on learning but their effectiveness is uncertain. This study aimed to identify the perceived benefits, impacts, operational practices, and challenges of running SBCs. Method. Case studies with 10 Australian primary schools from different socioeconomic and geographic areas. Focus groups or interviews were held with 142 participants including students, parents/carers, school staff, and funding body representatives between July 2016 and October 2017. Results. There were no eligibility criteria to attend SBCs with all students able to attend, regardless of household income. Thus, participating in the SBC was often reported as a matter of choice rather than a consequence of food insecurity. Participants, including children, discussed the many social benefits of SBCs (i.e., social eating, relationship building, school connection, and engagement) as well as perceived improved classroom behavior. Challenges for program delivery included resource limitations, particularly, the reliance on volunteers and sourcing food. Discussion/Conclusion. SBCs offered a range of benefits beyond their primary goal of addressing food security. SBCs were highly valued by members of the school community for their social, welfare, well-being, and educational benefits, but program sustainability is constrained by resource limitations.